Evidence for a regulatory loop between IFN‐γ and IL‐33 in skin inflammation. Issue 2 (31st January 2013) - Seltmann, Jenny; Werfel, Thomas; Wittmann, Miriam
Abstract Interleukin‐33 has recently gained much attention due to its role in allergic responses. It has been shown to amplify Th2 responses and to act as a damage‐associated molecular pattern. IL‐33 acts on a broad range of cells and has been proposed to link innate and adaptive features of allergic responses. It was the aim of this study to investigate this property of IL‐33 in the inflammatory response characterising atopic dermatitis (AD). We have analysed the response of skin‐resident cells derived from patients with AD and healthy donors with regard to the expression of IL‐33 and its receptor ST2. The functional impact of IL‐33 on CD4+ T cells was investigated. Keratinocytes and dermal fibroblasts clearly differ in their regulation of IL‐33. In fibroblasts, the concerted action of TNF‐α and IL‐1β was the strongest inducer, whereas IFN‐γ is clearly the key molecule that upregulates IL‐33 in keratinocytes with a more pronounced response of cells derived from patients with AD. Keratinocytes from patients with AD showed a markedly higher constitutive expression level of surface ST2. CD4+ T cells respond to IL‐33. Unexpectedly, IL‐33 failed to induce a significant secretion of IL‐5 or IL‐13. By contrast, high amounts of IFN‐γ were detectable if IL‐33 was added to the T‐cell receptor‐stimulated cells or in combination with IL‐12. These results suggest that IL‐33 and IFN‐γ are closely interlinked in epidermal AD inflammation. IFN‐γ induces IL‐33 in keratinocytes and IL‐33 acts on activated T cells to further increase the release of IFN‐γ, therefore contributing to drive skin inflammation towards chronic responses.